Primary Open-Angle Glaucoma Progression in Glaucoma Patients with Unchanged Topical Treatment over 3 Years – Retrospective Observational Cohort Analysis - Saruhan, Yasemin; Hasler, Pascal W.; Gugleta, Konstantin (Klinische Monatsblätter für Augenheilkunde, 2023)
Background Lowering intraocular pressure (IOP) is a mainstay of glaucoma therapy. It is, however, still an open question whether a comparable level of long-term IOP lowering achieved by different medications results in comparable protection for the retinal ganglion cells. The purpose of this study was to retrospectively analyze glaucoma damage progression in two cohorts of primary open-angle glaucoma patients with different and unchanged therapy over a period of 3 years, and the main objective of this study was to determine possible differences in terms of structural [retinal nerve fiber layer thickness (RNFL)] and functional [visual field (VF)] outcome.Patients and Methods The retrospective observational cohort analysis compared two differently treated groups of glaucoma patients with their original, at study entry, topical therapy unchanged over 3 years. The main endpoint was the time course of RNFL thickness and VF mean defect (MD).Results Twenty-one eyes were included in each group. The first group (21 eyes) was on a fixed combination of timolol and dorzolamide twice a day and the second group on one drop of prostaglandin analog, either latanoprost alone (15 eyes) or travoprost alone (6 eyes), in an unchanged regimen over a period of 3 years. IOP in mmHg at baseline and at 36 months was 11.9 ± 2.4 and 13.0 ± 2.1 in the first, and 12.9 ± 3.0 and 14.1 ± 3.2 in the second group, respectively. RNFL thickness values in micrometers were at baseline and at 36 months 77.8 ± 12.3 and 76.6 ± 15.2 in the first, and 77.5 ± 15.2 and 72.8 ± 14.5 in the second group, respectively. VF MD in dB were 1.7 ± 2.5 and 1.2 ± 2.9 in the first, and 0.9 ± 2.3 and 0.7 ± 2.6 in the second group, respectively.Conclusion Both groups had comparable baseline, as well as mean overall IOP. However, the course of IOP levels over time was different in the two groups, showing earlier and more pronounced long-term drift in the prostaglandin analog-treated group. RNFL thickness was comparable at baseline, however, RNFL thinning over time was more pronounced in the prostaglandin analog-treated group. There were no statistical differences between the groups in terms of VF MD at baseline and over time.
Keywords: glaucoma; POAG; intraocular pressure; retinal nerve fiber layer thickness